Annually resolved late Holocene paleohydrology of the southern Sierra Nevada and Tulare Lake, California. Issue 12 (17th December 2015) - Adams, Kenneth D.; Negrini, Robert M.; Cook, Edward R.; Rajagopal, Seshadri
Abstract: Here we present 2000 year long, annually resolved records of streamflow for the Kings, Kaweah, Tule, and Kern Rivers in the southwestern Sierra Nevada of California and consequent lake‐level fluctuations at Tulare Lake in the southern San Joaquin Valley. The integrated approach of using moisture‐sensitive tree ring records from the Living Blended Drought Atlas to reconstruct annual discharge and then routing this discharge to an annual Tulare Lake water balance model highlights the differences between these two types of paleoclimate records, even when subject to the same forcing factors. The reconstructed streamflow in the southern Sierra responded to yearly changes in precipitation and expressed a strong periodicity in the 2–8 year range over most of the reconstruction. The storage capacity of Tulare Lake caused it to fluctuate more slowly, masking the 2–8 year streamflow periodicity and instead expressing a strong periodicity in the 32–64 year range over much of the record. Although there have been longer droughts, the 2015 water year represents the driest in the last 2015 years and the 2012–2015 drought represents the driest 4 year period in the record. Under natural conditions, simulated Tulare Lake levels would now be at about 60 m, which is not as low as what occurred multiple times over the last 2000 years. This long‐term perspective of fluctuations in climate and water supply suggests that different drought scenarios that vary in terms of severity and duration can produce similar lake‐level responses in closed lake basins. Key Points: Two thousand year annually resolved streamflow reconstructions for Sierra Nevada rivers Reconstructed streamflow routed to Tulare Lake water balance model to enhance reconstructions Years 2012–2015 are driest consecutive 4 year period but not most severe drought in record